Business study mission to European union : "EU - ASEAN : trade and investment". - Hong, Jeff Heng Wah. (2011)
This paper addresses the Trade and Investment between ASEAN and EU against the backdrop of the Asian Economic Crisis. The research traces the ASEAN/Asia - EU trade-relationship since the establishment of the WTO till the Asian economic crisis. Trade barriers, such as tariffs and quotas, as imposed by various EU member states are expounded to give an insight of the complexities of trade activities ui the EU market. The chapter also identified the EU's key trading partners, EUrs trading patterns and the impact of the Asian crisis on EU-ASEAN trade. Lastly, the chapter wraps up by examining the characteristics of the flow of funds (i.e. foreign direct investment) between ASEAN and EU and its implications.